Comparison of Salivary Antioxidants and Oxidative Stress Status in Gestational Diabetes Mellitus and Healthy Pregnant Women - Ahmadi-Motamayel, Fatemeh; Fathi, Shima; Goodarzi, Mohammad T.; Borzouei, Shiva; Poorolajal, Jalal; Barakian, Yasamin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: One of the most common complications of pregnant women is gestational diabetes mellitus (GDM). Oxidative stress can play an important role in GDM. Objective: The aim of this study was to evaluate salivary antioxidants and oxidative stress markers in GDM. Methods: Twenty pregnant women with GDM and 20 healthy pregnant women with normal blood glucose test participated in this study. Five mL of unstimulated saliva samples were collected. Spectrophotometric assay was carried out for sialo-chemical analysis. Stata software was used for data analysis. Results: The GDM group exhibited no significant difference in salivary total antioxidant capacity and malondialdehyde compared to the healthy control group. All antioxidants markers, the uric acid, total antioxidant, peroxidase and catalase, decreased in GDM group that the difference of peroxidase and catalase was statistically significant. All of oxidative stress markers, the salivary malondialdehyde, total oxidative stress and total thiol, increased in GDM group. GDM group exhibited significantly higher salivary total oxidative stress levels. Conclusion: Catalase level was significantly lower and total oxidative stress was significantly higher. These two markers might have significant importance and might exhibit early changes compared to other factors in GDM. Some salivary antioxidants might have diagnostic, prognostic or therapeutic implications in GDM. Other studies with large sample size on salivary and blood samples need to be done to confirm these properties and salivary samples using instead of blood samples in GDM biomarkers changes.
Keywords: oxidative stress